The Employee: A Political History - Mummé, Claire (Relations Industrielles / Industrial Relations, 2015)
The article reviews the book, "The Employee: A Political History," by Jean-Christian Vinel
Keywords: Collective bargaining; EMPLOYEE: A Political History, The (Book); History; Industrial relations; Nonfiction; United States; VINEL, Jean-Christian